Do security analysts speak in two tongues? - Malmendier, Ulrike 1973-; Shanthikumar, Devin (Working paper series / National Bureau of Economic Research, 2007)
Why do analysts display overoptimism about the stocks they cover? According to the selection hypothesis, analysts pick their favorite stocks and are truly too optimistic. According to the conflict-of-interest hypothesis, analysts distort their view to maximize profits via commissions and underwriting business, in particular if affiliated with an underwriting bank. We analyze the concurrent issuance of recommendations and earnings forecasts to assess the relative importance of both explanations for affiliated and for unaffiliated analysts. First, we show that recommendations and forecasts reach different audiences. Small traders follow recommendations but not forecast updates; large traders discount recommendations and follow earnings forecasts. As a result, analysts may choose to distort recommendations but prove their analyst quality in their forecasts. The selection hypothesis implies, instead, a positive correlation between recommendation and forecast overoptimism. We find that, while affiliated analysts issue more optimistic recommendations than unaffiliated analysts, their earnings forecasts are more pessimistic. Moreover, forecast optimism is negatively correlated with recommendation optimism for affiliated analysts but positively for unaffiliated analysts. Similar discrepancies between the timing of recommendations and forecasts confirm that active distortion is a major explanation for the recommendation optimism of affiliated analysts.